Elaboración de una guía de estrategias metodológicas de educación ambiental en el manejo de residuos sólidos domiciliarios en la comunidad Cañas - Rivas Mendoza, George Mauricio (2017)
The Cañas Community suffers from a ignorance problem on the proper management of solid wastes, thus causing pollution to the social environment causing outbreaks of respiratory diseases with emphasis on the spread of insects, rodents and parasites detrimental to human health, for this reason the present investigation was developed, which met the proposed objectives, determining practical Environmental Education strategies for Cañas Community, which gave the following results. Of the total of the respondents, 80% don't know what solid household waste is and 20% know about it, said that the most generated solid residue in homes is plastic followed by household organic waste, cardboard, paper and glass. To meet the objective of training the community about the use of solid waste, were found a total of 74% respondents after giving the garbage or waste generated in housing talk. 12% of them didn't know what was given in the talk to the community, which is why the disease index points to diarrhea with 15.5 points, cancer with 13 points, and cholera with 11 points, are the diseases caused by household solid waste. In the construction of a practical guide to methodological strategies of environmental education on solid waste to improve local knowledge, the methodological guide will provide the community with unique strategies for environmental improvement, thus improving the environmental situation of the Cañas Community.